Analysis of Acidic Endogenous Phytohormones in Grapes by Using Online Solid-Phase Extraction Coupled with LC–MS/MS - Yu, Jian-Na; Meng, Qing-Yan; Liu, Wen-Jie; Lu, Ya-Ling; Ren, Xiao-Lin (Journal of chromatographic science, 2014)
Phytohormones play important roles in regulating numerous plant physiological and developmental processes, even during the postharvest storage period. In order to determine the functions and changes of gibberellins acid (GA3), indoleacetic acid (IAA), abscisic acid (ABA), indolebutyric acid (IBA) and jasmonic acid (JA) in grape berries during storage, an ultrasensitive method based on direct injection online solid-phase extraction coupled with high-performance liquid chromatography tandem mass spectrometry (LC–MS/MS) was developed. Grape berries were extracted with cold methanol. After centrifugation, the supernatants were concentrated with a vacuum centrifugal concentrator and injected into an online solid-phase extraction column. After the cleanup procedure, the analytes were determined by LC–MS/MS. The results showed that the linearity of the proposed method was 10–210 µg kg−1 for ABA, 20–200 µg kg−1 for IBA, 15–320 µg kg−1 for IAA, 20–320 µg kg−1 for GA3 and 3.0–90.0 µg kg−1 for JA. The limits of detection of the method were 0.71, 2.79, 0.94, 0.39 and 0.57 µg kg−1, respectively. The proposed method was successfully applied to the analysis of endogenous phytohormones in grape berries during the postharvest storage period.